Information Search for Bank Loan: A Study of Nepalese Entrepreneur - Gyawali, Prabin; Acharya, Nischal (Journal of Tilottama, 2023)
The paper attempts to investigate how consumers search information for bank loans and endeavors to provide insight into the different sources of information that entrepreneurs mostly used to grab detailed information regarding loan services. Based on data collection through structured questionnaires using correlation and regression analysis, results reveal that entrepreneurs mostly use bank sources as a source of information. Though Nepalese Entrepreneurs are aware of sources of information due to the non-availability of the required information as well as the trustworthiness of the obtained information they believe bank sources as trusted and reliable sources rather than other sources. The sample comprising of 130 employees in the Information Technology (IT) industry which were selected by non-probability sampling. It is concluded that Interest rate was found to be the most important criterion followed by the duration of the loan, monthly installment, payment flexibility, and processing fee by Nepalese entrepreneurs to decide the choice of bank.